Landasan filsafat ilmu modern: eksplorasi ontologi, epistemologi, dan aksiologi - Salsabila, Aqila (Maliki Interdisciplinary Journal, 2026)
The philosophy of science as the main foundation for understanding and developing human knowledge in the digital age, focusing on three key elements: ontology as reality, epistemology as knowledge, and axiology as value. Through philosophical analysis, practical examples, and contemporary relevance, this journal demonstrates the interaction of these three elements in forming the basis of dynamic science. Ontology divides the objects of science into material ones such as molecules, formal ones such as the law of gravity, and abstract ones such as energy, forming the identity of disciplines such as psychology and Islamic science, withpractical benefits in physics, sociology, and engineering. Epistemology examines the sources, methods, and validity of knowledge, emphasizing the integration of revelation and reason in Islamic epistemology, as well as complementary deductive and inductive methods for accurate and innovative knowledge in biology and mathematics. Axiology explores ethical, aesthetic, and moral dimensions to ensure science is beneficial, prevent misuse, and guide honest, sustainable, and socially responsible research. Overall, this integration promotes philosophical dialogue amid challenges such as artificial intelligence and climate change, affirming that this foundation is crucial for science that is holistic and meaningful.